Effect of 35% hydrogen peroxide on in-office bleaching against changes in tooth enamel hardness: Literature review - Asy-Syifa Brillian Avicenna; Christina Mahardika; Lira Wiet Jayanti (South East Asia Nursing Research, 2022)
Teeth bleaching is one of the treatments for teeth discolouration. Teeth bleaching can do in-home or in-office. The material for that use in-office bleaching is 35% hydrogen peroxide. Hydrogen peroxide is a chemical compound that is tough and has a micro molecule that can easily penetrate enamel tissue and dentin tissue. Bleaching with hydrogen peroxide in-office is now more attractive because can be faster to see the result. Bleaching with hydrogen peroxide when done repeat will make teeth more sensitive, and damage enamel tissue and dentin tissue.  The objective of this study is to know the influence of in-office bleaching using 35% hydrogen peroxide on microhardness enamel.  This research is made with a literature review with search engine google scholar, PubMed, and science direct. The results of 10 articles show the effectiveness of teeth discolouration after bleaching using 35% hydrogen peroxide in-office.  The reduction in enamel microhardness seen using SEM, knob and Vickers is visible although not significant. Based on the literature review research that has been carried out, it can be concluded that there is a reduction in enamel hardness after the in-office bleaching process by using 35% hydrogen peroxide.